Modulation of angiotensin II-mediated signalling by heparan sulphate glycosaminoglycans - Köppel, Hannes; Yard, Benito A.; Christ, Michael; Wehling, Martin; Woude, Fokko J. van der (Nephrology, dialysis, transplantation, 2003)
BACKGROUND: Heparin and angiotensin-converting enzyme inhibitors can be used as a therapeutic option in diabetic nephropathy (DN). Although the mode of action is poorly understood, both agents may retard the progression of DN. Previously, we demonstrated that angiotensin II (Ang II) has an inhibitory effect on the production of heparan sulphate proteoglycan (HSPG) in mesangial cells (MCs). We have now studied the influence of heparin on the Ang II-induced intracellular Ca(2+) release and activation of nuclear factor kappa B (NF-kappaB). METHODS: Human MCs were isolated from renal cortex and cultivated to measure Ca(2+) influx and NF-kappaB activation. RESULTS: Stimulation of MCs with 100 nM Ang II resulted in a rapid increase in the intracellular Ca(2+) concentration ([Ca(2+)](i)), followed by a decline to baseline level. The addition of heparin resulted in an oscillatory pattern of Ca(2+) influxes upon Ang II stimulation. Whereas the rapid increase in [Ca(2+)](i) was most likely due to release from intracellular stores, oscillations in [Ca(2+)](i) were dependent on the presence of extracellular Ca(2+). Heparin alone did not induce Ca(2+) influx. Both the initial increase and the subsequent oscillations in [Ca(2+)](i) could be blocked by losartan. In MCs with chemically or enzymatically altered membrane-associated heparan sulphate glycosaminoglycan (HS-GAG), Ang II stimulation resulted in [Ca(2+)](i) oscillations. Interestingly, in these cells, the addition of heparin or GAG completely prevented [Ca(2+)](i) oscillations. Heparin inhibited NF-kappaB activation in Ang II-stimulated MCs that expressed either normal or chemically altered GAG. CONCLUSIONS: These findings suggest that alterations in HS-GAG chemistry or metabolism under pathological conditions, such as DN, may have direct functional consequences for the local effect of Ang II.
Gesehen am 23.06.2022